Difusión de los personajes de la yumbada mediante la elaboración de material didáctico para los niños de 5 a 7 años en la Unidad Educativa Básica General ¨Quis Quis¨ de la ciudad de Latacunga. - Cruz Chuquitarco, Johan Patricio (2024)
In the educational context, the manipulative teaching materials used are puzzles, however, those available on the market refer to figures from foreign cartoons, and there are almost no puzzles that include the characteristics of local cultural identity. The objective of this research project is to develop didactic material for the teaching-learning processes of the Yumbada characters in children from 5 to 7 years old in the ¨Quis Quis¨ educational unit in the city of Latacunga. Ecuador. The development of the theoretical foundation was based on the review of academic and bibliographic documentation of books and scientific articles to obtain the importance and functionality of the teaching material in the learning-teaching process. In such a way that a methodology was proposed with an inductive method, with a descriptive and deductive scope. Consequently, techniques were applied for data collection such as interviews for teachers and artisans (Luis Quimbita). For this reason, an analysis was carried out of the information collected from the field study that was carried out to record the evidence of the teaching materials and also about the festival, in this field investigation it was determined that the teachers use outdated materials for teaching the scope of subjects and materials that do not correspond to the educational needs of infants, hindering the development of their skills within this field. Faced with this, a teaching material was developed, where sketching, iconographic analysis, digitization were developed, in the same way, its flexibility, manipulable, versatile, entertaining, was analyzed, and then it was developed through intercultural graphics that promotes learning. of the Yumbada festival. Accordingly, with the analysis it is concluded that through the game the images describe the ideal characteristics for learning in boys and girls, with this it was possible to obtain the learning and skill that is desired to be developed through participation activities, development in the education of children and where teachers already choose material for their practices in student development. Furthermore, it is a tool that allows you to visualize the colossal diversity and richness of expressions of its heritage, promoting knowledge and understanding of the celebration.